Peran Bumdes Dalam Pemberdayaan Ekonomi Masyarakat Desa Di Bagian Barat Dan Utara Kabupaten Sumba Timur - Babang, Noti; Praing, Mesakh Landu; Kahumbu, Gerald Antonio Hendrian; Lobo, Dirga Noveria Edelweiss; Ramompas, Yuvensius; Renggo, Yuniarti Reny (ProBisnis : Jurnal Manajemen, 2025)
This research aims to explore the role of Village-Owned Enterprises (BUMDes) in empowering the village economy in the western and northern regions of East Sumba Regency. The study employs a qualitative descriptive approach to analyze how BUMDes carry out their functions through various business units, including poultry farming, agriculture, savings and loan services, clean water provision, tourism, and rental services. Data were collected through in-depth interviews, observations, documentation, and literature review. The results show that these BUMDes have made significant contributions to increasing local income, creating job opportunities, and reducing dependency on external markets. Socially, BUMDes also fosters community participation and solidarity by involving youth and women in the economic process. However, several challenges were identified, including low public awareness, lack of competent human resources, weak organizational structure, and limited infrastructure. Strengthening BUMDes requires continuous capacity building, better institutional governance, and improved infrastructure to support sustainable village development.